2006
DOI: 10.1128/mcb.02380-05
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Desmoglein 2 and Activated Leukocyte Cell Adhesion Molecule as Substrates of ADAM17 and ADAM10 by Difference Gel Electrophoresis

Abstract: In contrast with the early view of metalloproteases as simple extracellular matrix-degrading entities, recent findings show that they are highly specific modulators of different signaling pathways involved, positively or negatively, in tumor development. Thus, before considering a given metalloprotease a therapeutic target, it seems advisable to characterize its function by identifying its repertoire of substrates. Here, we present a proteomic approach to identify ADAM17 substrates by difference gel electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 35 publications
1
111
0
Order By: Relevance
“…ADAM family members have been shown to cleave classic cadherins, and Dsg2 was also recently identified as a substrate of ADAM10 and 17 (Bech-Serra et al, 2006). To test whether either of these ADAM family members is responsible for Dsg2 cleavage in SCC68 cells, we introduced ADAM10 or 17 small interfering RNA (siRNA) into SCC68 cells.…”
Section: Dsg2 Processing and Trafficking Is Adam-dependentmentioning
confidence: 99%
“…ADAM family members have been shown to cleave classic cadherins, and Dsg2 was also recently identified as a substrate of ADAM10 and 17 (Bech-Serra et al, 2006). To test whether either of these ADAM family members is responsible for Dsg2 cleavage in SCC68 cells, we introduced ADAM10 or 17 small interfering RNA (siRNA) into SCC68 cells.…”
Section: Dsg2 Processing and Trafficking Is Adam-dependentmentioning
confidence: 99%
“…Recently, Bech-Serra et al (2006) have shown that ADAM17 acts as a proteolytic sheddase of ALCAM. Rosso et al (2007) observed that this process is involved in the motility of epithelial ovarian carcinoma cells.…”
mentioning
confidence: 99%
“…Substrates include a number of ligands for the EGF receptor (EGFR) and TNF-α , giving ADAM17 its alternative name TNF-α -converting enzyme. ADAM17 has additionally been shown to play a key role in ligandindependent Notch signalling, and in the shedding of cell adhesion molecules including DSG2 (Gschwind et al, 2003;Klessner et al, 2009;Pruessmeyer & Ludwig, 2009;Sahin et al, 2004;Bech-Serra et al, 2006).…”
Section: Adam17mentioning
confidence: 99%